Effects of phloroglucinol and resorcinol on In vitro vegetative growth enhancement and lethal browning reduction in lang banana - Ramlan, Nurhana Nadia (2019)
Browning is ue culture industry. The formation of browning is due to the formation of dark exudates around explants, in which it can inhibit explant proliferation. Phenolic compounds such as phloroglucinol (PG) and resorcinol are known to have an ability to reduce browning in food and cosmetic products. Hence, both phenolics were used in this study to determine their capability to reduce browning and at the same time to enhance growth of in vitro Lang banana. The total soluble protein content, gene expression level of antioxidant (catalase (CAT), ascorbate peroxidase (APX) and peroxidase (POD)), browning- inducing (phenylalanine ammonia lyase (PAL) and polyphenol oxidase (PPO)) and lignin-biosynthetic (MYB31, MYB58, cinnamoyl coA reductase (CCR), catechol-O- methyltransferase (COMT), cinnamyl aldehyde dehydrogenase (CAD) and p– coumarate hydroxylase (C3H)) genes as well as their enzymes activities were also observed on the early stage of browning of Lang banana explants grown on selected media. To achieve the objectives, Murashige and Skoog (MS) basal media supplemented with B5 vitamin, different concentrations of phenolics (PG or resorcinol), different concentrations of cytokinins (6-benzylaminopurine (BAP) or kinetin) and auxin (α-naphthalene acid (NAA)) were used. The growth of each explant was recorded by determining the number of shoots, number of buds and number of roots every week for 12 weeks. The visual degree of browning was also recorded. The highest percentage of explants belong to mild browning was observed from media containing NAA (0 to 0.013 mM) + resorcinol at range of concentrations of 1.0 to 2.5 mM (60 to 100%). Meanwhile, the combination of NAA (0 to 0.013 mM) + PG at range of concentrations from 1.0 to 2.5 mM showed lower percentage of mild browning (0 to 40%) compared to NAA + resorcinol media. The medium containing 0.023 mM kinetin + 0.5 mM resorcinol produced the highest mean number of shoots (6.2±1.20). Meanwhile, the medium containing 0.022 mM BAP + 0.5 mM PG showed the highest bud proliferation (7.8±0.45). The medium containing 0.005 mM NAA + 1.5 mM PG produced the highest number of roots (30.4±1.43). Among the media tested six media were categorized into mild (MS medium containing 0.008 mM NAA + 0.5 mM PG (MBPG) and MS medium containing 0.005 mM NAA + 2.0 mM resorcinol (MBR) media), intermediate (MS medium containing 0.023 mM kinetin + 0.011 mM NAA + 0.5 mM PG (IBPG) and MS medium containing 0.023 mM kinetin + 0.5 mM resorcinol (IBR)) and severe browning inducing media (MS medium containing 0.022 mM BAP + 0.013 mM NAA + 2.5 mM PG (SBPG), and MS medium containing 0.022 mM BAP + 0.013 mM NAA + 2.5 mM resorcinol (SBR)). The highest total soluble protein content was observed in SBPG explant (40.46±0.01 mg/g FW). The highest CAT (356.26±0.02 µmol/min/mg) and APX (5893.18±0.20 µmol/min/mg) activities were observed in MBPG explant. Meanwhile, the highest POD, PPO, C3H and PAL activities were determined in SBR explants (13849.88±0.06, 2639.52±0.02, 1332.38±0.00 and 132.57±0.01 µmol/min/mg, respectively). Among the genes tested, the highest PAL expression was found in SBPG explant (225.31-fold). Meanwhile, the highest expression of APX and PPO was observed in IBR explants (4887.9- and 37.33-fold, respectively). The POD, COMT and CCR expression were up-regulated in MSO9 explant (49.57-, 302.49- and 89.30-fold, respectively), while the highest expression of C3H, CAD and CAT (44.36-, 11.22- and 29.33-fold, respectively) were observed in MBR explant. The expression of MYB31 was highly expressed in MBPG explant (9.07- fold) while the expesssion of MYB58 was found the highest in MSO7 explant (19.39- fold). Hence, the incorporation of the PG and resorcinol into different media formulations is proven can reduce browning and improve proliferation of in vitro Lang banana. The presence of antioxidant, browning-inducing and lignin-biosynthetic enzymes as well as their mRNA transcripts in the early browning explants suggest their involvement in scavenging free radical, reducing browning and enhancing lignin production. Therefore, the best media produced from this study can help plant tissue culture laboratories to mass produce Lang banana seedlings. The analyzed genes can be used as biomarker to develop browning resistant Lang banana in the near future.